The Influence of Online Social Identity and Digital News Literacy on Students' Critical Thinking From a Cyberpsychology Perspective - Putri Shabri Nurbaeti; Abdullah Azzam Al Afghani (LPPM Universitas 17 Agustus 1945 Samarinda, 2026)
Students living in the digital age face challenges and are directly affected by use of digital media. If not used wisely, it will affect students’ critical thinking processes. This study was conducted to determine the influence of online social identity and digital news literacy on students’ critical thinking. The research design was quantitative correlational to determine the extent of the influence of online social identity and digital news literacy on students. The subjects this study were 143 active students aged 18-25 years from various universities in Indonesia and a total of 104 data used in the final anaylsis after the screening process and removal outliers. Data collection in this study used the IBRS (Identity Reinforcement Scale) to measure online social media identity, PSMLS (Perceived Social Media Literacy) to measure digital news literacy, and the Complex Thinking-21 Scale to measure critical thinking. The results of the study indicate that online social media identity and digital news literacy have a positive effect on students’ critical thinking, but online social identity does not have a simultaneous effect. Together, these two variables account for 13,9% of the variance in students critical thinking, which means that there may be other factors that also influence students’ critical thinking beyond scope of this study. These findings indicate that cyberpsychology, chataracterized by increased digital literacy, influence student critical thinking, with online social identity serving as a psychological dinamic in social media social use. It is hoped tht these research findings will serve as a foundation for developing interventious based on digital lieracy and students information evaluation skills in the digital age.